2022
DOI: 10.3390/su14138145
|View full text |Cite
|
Sign up to set email alerts
|

The Monetary Value of Corporate Social Responsibility: The Impact of Tea Trees Growing Project between Corporates and Taiwan’s Aboriginal Farmers on Consumers

Abstract: The first hypothesis of this study is to dissect the factors that impact consumers’ preference toward a specific corporate social responsibility (CSR) project via the framework of the theory of planned behaviour (TPB). The second hypothesis is to evaluate a monetary value for CSR among consumers through their WTP. The willingness to pay (WTP) in relation to those influential factors is used to represent the monetary value of CSR for the tea tree growing project implemented by corporates among indigenous tribal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The next strategy, besides encouraging the implementation of CSR by LLCs and SOEs in the form of community development, is also needed to encourage cooperatives to perform social and environmental responsibility, better known as CoopSR. The social responsibility practices have been performed by every type of company and in many ways [49], including by cooperatives. The term CoopSR was first introduced by Develtere [50] and Harris [51] in 2005.…”
Section: Csr and Coopsr Implementation Policy Strategy In Creating A ...mentioning
confidence: 99%
“…The next strategy, besides encouraging the implementation of CSR by LLCs and SOEs in the form of community development, is also needed to encourage cooperatives to perform social and environmental responsibility, better known as CoopSR. The social responsibility practices have been performed by every type of company and in many ways [49], including by cooperatives. The term CoopSR was first introduced by Develtere [50] and Harris [51] in 2005.…”
Section: Csr and Coopsr Implementation Policy Strategy In Creating A ...mentioning
confidence: 99%
“…Humans are inherently influenced by a variety of contextual elements, and different attributes and features offered in a good (Al Jarah & Emeagwali, 2017; Lissner & Mayer, 2020). WTP demonstrates how much a consumer is prepared to forego in order to obtain the bundle of characteristics that a product or service provides, and it is thus an outcome that allows to measure the worth of CSR for consumers in the market (Lee et al, 2022). Becchetti et al (2020) found that socially, environmentally and legally responsible products have a significant positive effect on consumers' WTP.…”
Section: Introductionmentioning
confidence: 99%